The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3390/v9050104
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Infection of Enterovirus D68 Leading to Lower Respiratory Tract Pathogenesis in Ferrets (Mustela putorius furo)

Abstract: Data from EV-D68-infected patients demonstrate that pathological changes in the lower respiratory tract are principally characterized by severe respiratory illness in children and acute flaccid myelitis. However, lack of a suitable animal model for EV-D68 infection has limited the study on the pathogenesis of this critical pathogen, and the development of a vaccine. Ferrets have been widely used to evaluate respiratory virus infections. In the current study, we used EV-D68-infected ferrets as a potential anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…A transient viremia developed in ferrets after intranasal inoculation, and virus-specific RNA was detected in feces from infected animals, neither of which is observed during most human infections. No neurological disease developed, nor did virus replicate in this animal model of EV-D68 infection (60).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A transient viremia developed in ferrets after intranasal inoculation, and virus-specific RNA was detected in feces from infected animals, neither of which is observed during most human infections. No neurological disease developed, nor did virus replicate in this animal model of EV-D68 infection (60).…”
Section: Discussionmentioning
confidence: 95%
“…Four mouse models of EV-D68 infection have been established (13, 35, 5961). One model examined the immune response within the respiratory tract elicited after intranasal inoculation with EV-D68 using 8- to 10-week-old wild-type BALB/c mice; however, no virus replication was observed in these animals (61).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support that EV-D68 mostly causes respiratory illness. 35,37,38 EV-D68 also has tropism of motor nerve cells and may lead to neurological involvement (Table 3). 39…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Animal study found that EV-D68 infection induces inflammation and diffuse alveolar hemorrhage in the lungs and leads to lung injury at the middle and late stages of infection. 38 Clinically, patients may have severe respiratory illness which needs hospitalization and even intensive care or ventilator support. 19,24 Common features of hospitalized patients include tachypnea, hypoxia, asthma attack, pneumonia or acute respiratory distress syndrome.…”
Section: Mild To Moderate Respiratory Illnessmentioning
confidence: 99%
“…Previously Patel et al found that four to six week-old cotton rats were permissive to transient EVD68 replication following intranasal infection; however, the infectious virus was cleared from the nose and lung tissues 48 h post infection, and no clinical symptoms or death were observed in the rats [ 20 ]. Similarly, intranasal infection of EVD68 resulted in minimal clinical symptoms in ferrets [ 21 ]. Therefore, the two animal models are not suitable for evaluation of EVD68 vaccines and antiviral agents.…”
Section: Introductionmentioning
confidence: 99%